2022
DOI: 10.1200/op.21.00836
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Electronic Psychosocial Screening Among Caregivers in Pediatric Oncology

Abstract: PURPOSE: This study aimed to evaluate the reach and implementation of an electronic psychosocial screening program among caregivers of pediatric oncology patients, as well as characterize caregiver distress. METHODS: Participants (N = 2,013) included caregivers of patients age 0-17.99 years presenting across 9,280 outpatient oncology visits (median = 2; range = 1-52) from September 2018 to June 2019. At check-ins, caregivers electronically completed the pediatric distress thermometer via a patient-facing elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Parents provide informal care to their child during and after cancer therapy, 10 and they must balance competing priorities such as work and caregiving to other family members. 11 In addition to witnessing their child’s suffering, the uncertainty of cancer prognosis and financial hardship resulting from medical expenses and lost income may intensify parental distress and trigger MH problems 11 , 12 , 13 and may also become barriers to parents seeking needed MH care. Without timely effective treatment, MH conditions may not only drive morbidity and mortality among parents but also undermine the well-being of their children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents provide informal care to their child during and after cancer therapy, 10 and they must balance competing priorities such as work and caregiving to other family members. 11 In addition to witnessing their child’s suffering, the uncertainty of cancer prognosis and financial hardship resulting from medical expenses and lost income may intensify parental distress and trigger MH problems 11 , 12 , 13 and may also become barriers to parents seeking needed MH care. Without timely effective treatment, MH conditions may not only drive morbidity and mortality among parents but also undermine the well-being of their children.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Professional societies have developed standards of care that recommend routine psychosocial assessment and interventions for caregivers of children with cancer. 16 Although studies have examined self-reported MH status in caregivers of children with cancer, 10,12,13,[16][17][18] empirical evidence of recommended psychosocial service utilization among caregivers is lacking. We hypothesized that utilization of MH services would be higher among parents of children with cancer than in the general parent population.…”
Section: Introductionmentioning
confidence: 99%